Volatilization of Dicamba Diglycolamine Salt in Combination with Glyphosate Formulations and Volatility Reducers in Brazil - Carbonari, Caio Antonio [UNESP]; Costa, Renato Nunes [UNESP]; Giovanelli, Bruno Flaibam [UNESP]; Bevilaqua, Natalia Cunha [UNESP]; Palhano, Matheus; Barbosa, Henrique; Lopez Ovejero, Ramiro Fernando; Velini, Edivaldo Domingues [UNESP] (MDPI, 2022)
Dicamba can be included in weed management programs for Brazilian agricultural crops, such as Conyza spp. and Amaranthus spp., and it is essential to implement good management practices that include salts with low volatility levels and appropriate associations to maintain volatility at acceptable levels. The objective of this study was to evaluate the volatilization of dicamba diglycolamine (DGA) salt associated with different glyphosate salts and volatility reducers. Laboratory and field studies were conducted with the application of DGA alone and in mixtures with three glyphosate formulations (potassium salt, ammonium salt, and di-ammonium salt) with and without a volatility reducer. Under laboratory conditions, the sprayed targets (corn straw) were sent to a vapor collection system for subsequent determination of the amount of volatilized dicamba. In the field, the treatments were applied in a tray containing clay soil, and then, these trays were arranged in soybean rows for 48 h under plastic tunnels. The plant injury and the concentrations of the dicamba in the soybean plants at different distances from the tray were determined. The methodologies used in this study were adequate for understanding the volatility of DGA. The volatility of the dicamba DGA salt used was reduced and was managed through the use of volatility reducers and the correct formulation of glyphosate in the mixture. The VR was efficient in reducing the volatility for dicamba alone and DGA in combination with all glyphosate salts. The combination of dicamba DGA salt with glyphosate potassium salt and a volatility reducer was the mixture with the lowest volatility and is the most suitable combination to recommend to farmers.
Keywords: adjuvants; auxin herbicide; formulation; soybean; vapor